491 Short-term prognostic implications of left ventricular myocardial work indices in advanced heart failure patients treated with repetitive Levosimendan infusions. (8th December 2021) - Fazzari, Fabio; Cannata, Francesco; Banfi, Daniele; Pellegrino, Marta; Pagliaro, Beniamino; Loiacono, Ferdinando; Mantovani, Riccardo; Donghi, Valeria; Curzi, Mirko; Maurina, Matteo; Condello, Francesco; Liccardo, Gaetano; et al.
Abstract: Aims: Repetitive Levosimendan treatment in advanced heart failure patients has not been investigated yet via myocardial work indices (MWI), which could more accurately detect the effects of this both inotropic and vasodilatory drug. The aims of this study were (1) to describe variations of myocardial work indices, as a consequence of repetitive Levosimendan infusions and (2) to assess the prognostic value of myocardial work parameters in these patients. Methods and results: Fourteen patients with advanced heart failure treated with intermittent in-hospital levosimendan infusions were prospectively included. Clinical, laboratory, and echocardiographic assessment were performed before and after every Levosimendan infusion. The primary endpoint was a composite of any episode of decompensated HF, urgent HF rehospitalization, cardiogenic shock, cardiac arrest and cardiovascular death at 4–6 weeks follow-up after each planned infusion. During follow-up (mean: 150 ± 99 days) a total of 37 infusions were performed and a total of 11 cardiovascular events occurred. Global constructive work (GCW), global work efficiency (GWE), and global work index (GWI) increased after Levosimendan infusion in 62.2%, 73.0%, and 70.3% of cases, with significant differences between patients with and without outcomes [delta GCW: −7.36 mmHg% (134.12) vs. 113.81 mmHg% (204.41), P  = 0.007; delta GWE: −3.27% (8.38) vs. 4.30% (5.58), P  = 0.002]. Delta value of GWE showed the largest area under curve (AUC: 0.82, 95% CI: 0.64–1.00, P = 0.002) for outcome prediction with a cut-off point of 0.5%. Independent prognostic value of GWE variation was confirmed in multivariable regression models (OR: 0.825, 95% CI: 0.702–0.970, P = 0.02). Conclusions: GWE and GCW provided incremental and independent prognostic value at short-term follow-up over traditional echocardiographic parameters. The differentiation of patients into 'workers', whose GWE improved after Levosimendan infusion, and 'non-workers', who failed to improve their GWE, permitted to identify patients at higher risk of forthcoming cardiovascular events. Monitoring these patients with MWI may have relevant clinical implications.